Revealed of A novel Allele in Wasit – Iraqi Population - K. AL-Rubai, Haider; M. AL-Zubaidi, Mohammed; K. Ibrahem, Hala; Mohammed, Ali; Rashed, Sahar (Iraqi Journal of Science, 2023)
The developments in forensic DNA technology have led us to perform this study in Iraqi population as reference database of autosomal Short Tandem Repeat (aSTR) DNA markers . A total of 120 unrelated individuals from Wasit province were analyzed at 15 STR DNA markers. Allele frequencies of DNA typing loci included in the AmpFlSTR1 IdentifilerTM PCR Amplification Kit panel from Applied Biosystems (D3S1358, vWA, FGA, D8S1179, D21S11, D18S51, D5S818, D13S317, D7S820, TH01, TPOX, CSF1PO, D19S433, D2S1338, D16S539) and several forensic efficiency statistical parameters were estimated from all the sample. the combined Matching Probability (CMP) using the 15 STR genetic loci in Iraqi population was estimated at 1 in 2.08286E-18 and the Combined Discrimination Power (CDP) was greater than 0.9999999 ,Combined Exclusion Probability (CEP) was 0.98350917 which should be sufficient for the identification of any individual.